Decadal Variations of Wood Decay Hazard and El Niño Southern Oscillation Phases in Iran - Helali, Jalil; Momenzadeh, Hossein; Saeidi, Vahideh; Brischke, Christian; Ebrahimi, Ghanbar; Lotfi, Mohammad (Frontiers in Forests and Global Change, 2021)
The intensive use of wood resources is a challenging subject due to urbanization, population growth, and biodegradability of wooden materials. The study of climatic conditions and their effects on biotic wood degradation enlightens tracking the trend of wood decay and decomposition at regional and global scales to predict the upcoming responses for sustainable wood preservation. Thus, it yields an overview for decision makers to create a precise guideline for protecting wooden structures and prolonged service life. This study investigates the decay hazard in Iran, its decadal changes, and how it is affected by different phases of the El Niño Southern Oscillation (ENSO). Therefore, the risk for fungal decay of wood was estimated based on the Scheffer Climate Index (SCI) at 100 meteorological stations located in Iran, for the period 1987-2019 (separately for first, second and third decade as decadal analysis). Subsequently, SCI value trends were analyzed using the Mann-Kendall and the Sen’s slope method. Finally, the relationship between SCI and climatic parameters (temperature and precipitation) was explored. Generally, the SCI fluctuated between 2 to 75 across the region. The decay risk was ranked as low in most parts, but moderate in the northern part of the country along the Caspian Sea coastlines. Decadal analysis demonstrated that the highest mean SCI values took more place in the third decade (58% of stations) and the lowest mean SCI values in the second decade (71% of stations). Furthermore, the highest and the lowest SCI values occurred at 70% and 66% of stations in El Nino and Neutral phase, respectively. Trend analysis of SCI values showed that large parts of several provinces exhibited a significantly increasing decay hazard with a mean SCI of 2.9 during the period of 33 years. In this study, the effect of precipitation on SCI was confirmed to be greater than the temperature. Our findings can provide a better insight into the potential wood decay risk, analysis, and its regional distribution to prolong the wood service life and durability by preservative treatments.